The Influence of Gamification on Problem Based Learning in Improving the Quality of Physical Education and Sports Learning at the Elementary School Level: Motivational Formation of Social and Cultural Character in Rural Papua Indonesia - Carolus Wasa; Adi Sumarsono; Thadius Yambedoan; Dani Nurcholis (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2025)
This study analyzes the effect of Gamification Based Learning (GBL) on creative thinking ability and collaborative skills of students in rural Papua. By using 27 elementary schools in rural papua indonesia. data taken directly in the field through valid test results without flaws, this study ensures that all variables, including increasing the motivation of social character of students in rural papua with the application of gamification in sports learning are filled in completely, and can provide valid data. The results of the analysis showed that the application of gamification in sports learning significantly increased students' creativity. Hypothesis testing using t-statistics showed a significance value (p-value) of 0.000, well below the threshold0.005, indicating a significant difference between the experimental and control classes. In the experimental class, 100% of students moved to the